In vivo evaluation of porous titanium implants with biomimetic coating - Machado, Ana Cristina P. [UNESP]; Oliveira, Marize V.; Pereira, Robson P.; Carvalho, Yasmin R. [UNESP]; Cairo, Carlos Alberto A. (Trans Tech Publications, 2009)
The osseointegration of porous titanium implants was evaluated in the present work. Implants were fabricated from ASTM grade 2 titanium by a powder metallurgy method. Part of these implants were submitted to chemical and thermal treatment in order to deposit a biomimetic coating, aiming to evaluate its influence on the osseointegration of the implants. The implants were characterized by Scanning Electron Microscopy (SEM), Electron Dispersive X-Ray Spectroscopy (EDS) and Raman Spectroscopy. Three coated and three control (uncoated) implants were surgically inserted into thirty albino rabbits' left and right tibiae, respectively. Tibiae samples were submitted to histological and histomorphometric analyses, utilizing SEM, optical microscopy and mechanical tests. EDS results indicated calcium (Ca) and phosphorous (P) at the surface and Raman spectra exhibited an intense peak, characteristic of hydroxyapatite (HA). Bone neoformation was detected at the bone-implant interface and inside the pores, including the central ones. The mean bone neoformation percentage in the coated implants was statistically higher at 15 days, compared to 30 and 45 days. The mechanical tests showed that coated implants presented higher resistance to displacement, especially after 30 and 45 days.
Keywords: Biomimetic coating; Implant; Osseointegration; Porosity; Porous titanium; Auger electron spectroscopy; Biomimetics; Bone; Calcium; Coatings; Explosive actuated devices; Heat treatment; Hydroxyapatite; Metallurgy; Optical microscopy; Phosphorus; Raman scattering; Raman spectroscopy; Scanning electron microscopy; Spectrum analysis; Titanium